Hard cash: A post-disciplinary digest - Angus Cameron; Stephen Dunne (Finance and Society, 2015)
May 6th 2010, 2.45pm. The Dow Jones Industrial Average falls by nearly 1000 points, trillions of dollars were 'wiped' from the value of major US stocks and, for a few long minutes, the global economy was on the brink of a new catastrophe. Then 'it' all came back. It remains unclear what, exactly, caused the 'Flash Crash'. More worryingly, it has always been unclear what, exactly, was 'lost' and 'regained' in those apocalyptic moments. This is as much a philosophical, anthropological, and aesthetic concern as it is also an economic or financial one - trillions of what, exactly?
Keywords: 300